Review Article: Global Governance in a Complex World (Frontiers in Law, 2023)
This essay reviews the literature on international regime complexity and international institutional complexity published in three high impact journals between 2009 and 2022. The analysis identifies conceptual ambiguities as it discusses the definitions of complexity proposed by the scholarship. The goal is to highlight indicators of complexity in international politics, with a focus on global governance. These indicators are observable, subject to measurement and comparison. Based on some of these indicators, the essay explores the relationship between complexity and compliance -- or to what extent states implement the legal commitments that they adopted internationally, in light of the literature. The essay makes an original contribution when it chronicles and organizes the scholarship on complexity in terms of agency, scope, and effectiveness. It also analyses the presence and levels of a hierarchical relationship amongst the elements that make up a complex regime or institution. The Scholarship reviewed here constitutes essential reading for any researcher that is interested in global governance, international law, and compliance.